GAYA BAHASA DALAM LIRIK-LIRIK LAGU LINKIN PARK ALBUM A THOUSAND SUNS - PELEGER, ZUL FAHMY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRCTÂ Â Â Â Â Â Â Â Â Â Â Â This skripsi is entitled â€œLanguage Style in Â Song Lyrics of Linkin Park Album A Thousand Suns ( stylistics analysis)â€. Language style is a way of expressing oneself through language. Language style Â allows us to judge others through character and abilities of someone who uses the language.Â Â Â Â Â Â The aim of this research is classify and analyze language style in lyrics of song Linkin Park album A Thousand Suns.The writer uses descriptive methode. This Â research focuses on figure of comparison, figure of opposition, figure of connection, figure of repetition. The writerÂ identifies the data by reading Â the lyrics scriptÂ after downloading from the internet, classifying and analyzing the data he uses the theory of Â Halliday.Â Â Â Â Â Â Â Â Â Â Â The result of this research shows that there are 8 language style in used the lyrics Linkin Park album A Thousand Suns from 9 songs is simile (4), metaphor (1), personification (8), antitesis (4), hiperbole (15), oksimoron (4), metonymy (4), repetition (7). So the conclusion that the use language style in lyrics of song Linkin Park Â album A Thousand Suns is the most widely used is figure of opposition : Hyperbole.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords : Language Album, A Thousand suns Album.